Changes in honey bee nutrition after exposure to radiofrequency electromagnetic field - P. Migdal; M. Plotnik; P. Bieńkowski; A. Murawska; E. Berbeć; P. Sobkiewicz; K. Zarębski; K. Latarowski (The European Zoological Journal, 2024)
Urban beekeeping has gained interest in recent years. Bees placed in cities, on the roofs of buildings, are exposed to many different sources of electromagnetic fields of different frequencies and intensities. Knowledge about the impact of electromagnetic fields on the physiology and behavior of insects (including honey bees) is limited. Hence, one of the first steps was to check how radiofrequency electromagnetic fields affect honey bees’ nutrition. The level of total proteins, glucose, triglycerides, and TAS activity in bee hemolymph was analyzed. This is because they indicate the honey bee’s nutrition level. The experiment involved 2-day-old Carniolan worker honey bees (Apis mellifera carnica L.). The bees were exposed to fields of 12 V/m, 28 V/m, and 61 V/m for 0.25, 1 and 3 h. Hemolymph was taken from 40 alive worker honey bees from each group immediately after exposure, by removing the antennae with sterile tweezers. The activity of biochemical markers (total proteins, TAS, and triglycerides) in the bee hemolymph in 12 V/m and 28 V/m groups showed statistically significant differences compared to the control group in most cases. According to our own research, radiofrequency electromagnetic fields disturb honey bee nutrition. The changes in the analyzed indicators may have long-term effects.